Malaysia agricultural products - export prospects and problems - Gibbons, E. T.; Mohamed, Zainal Abidin (1986)
The changing concepts of marketing and their implications for Malaysian agriculture are examined. The main dimensions and characteristics of agricultural and related exports - and of replaceable imports - are discussed. Some past and ongoing marketing opportunities are considered and pitfalls highlighted. Recommendations are made to government and its instutions; agricultural and related firms and smallholders; employers' associations; and, lastly, the Agricultural Institute of Malaysia. Generally speaking, agricultural firms are advised to first capture all the feasible sections of the domestic market. From resultant firm base, export markets can be tackled with a reasonable degree of confidence.